Study on Prescription Technology of Sofosbuvir/Ledipasvir Tablet (Communications in Computational Chemistry, 2018)
Clone the Harvoni$^{\rm TM}$(Sofosbuvir/Ledipasvir) tablet manufactured by GileadSciences, Inc. and screen out the best formula of prescription, to make the pesticideeffect of prepared tablet was equal to the original tablet. Methods: Based on theprescription of HarvoniTM manufactured by Gilead Sciences, Inc., the compatibility testof the excipient with the active ingredient was carried out. The stability of self-madesamples and reference preparations were investigated, which includes hightemperature, high humidity and light conditions. According to the above test, the mostreasonable prescription process was chosen. Results: The determined prescriptionprocess contained sofosbuvir (400mg), ledipasvir (90mg), copovidone (97.5mg),croscarmellose sodium (50mg), microcrystalline cellulose (115mg), lactosemonohydrate (230mg), magnesium stearate (7.5mg), gum arabic(10mg), opadry filmcoating powder, and purified water. Conclusion: The determined prescription processwas stable and the pesticide effect of prepared tablet was equal to the original tablet, sothe prescription design was reasonable.
Keywords: Harvoni$^{\rm TM}$; Prescription Technology; Sofosbuvir.